2021
DOI: 10.1002/alz.12502
|View full text |Cite
|
Sign up to set email alerts
|

Tau phosphorylation sites serine202 and serine396 are differently altered in chronic traumatic encephalopathy and Alzheimer's disease

Abstract: Introduction Chronic traumatic encephalopathy (CTE) is a neurodegenerative tauopathy associated with repetitive head impacts (RHI) typically sustained by contact sport athletes. Post‐translation modifications to tau in CTE have not been well delineated or compared to Alzheimer's disease (AD). Methods We measured phosphorylated tau epitopes within dorsolateral frontal cortex from post mortem brains with neither CTE nor AD (n = 108), CTE (n = 109), AD (n = 223), and both CTE and AD (n = 33). Results Levels of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 93 publications
(114 reference statements)
0
15
0
Order By: Relevance
“…While three repeat and four repeat tau species are present in both AD and CTE [22,23], unique folding patterns of tau have been reported to predominate in CTE as compared to AD [24]. Beyond a limited number of studies, little is known regarding the exact tau species present in CTE and how they can be distinguished at the epitope level from the tauopathy of AD, though we recently found that both ptau 202 and p-tau 231 are associated with increased years of RHI from American football [25]. Increased p-tau 231 levels in CTE may be due to tau leakage from cells into the CSF, which may be present even relatively early on in the disease course when clinical symptoms are relatively mild.…”
Section: Discussionmentioning
confidence: 99%
“…While three repeat and four repeat tau species are present in both AD and CTE [22,23], unique folding patterns of tau have been reported to predominate in CTE as compared to AD [24]. Beyond a limited number of studies, little is known regarding the exact tau species present in CTE and how they can be distinguished at the epitope level from the tauopathy of AD, though we recently found that both ptau 202 and p-tau 231 are associated with increased years of RHI from American football [25]. Increased p-tau 231 levels in CTE may be due to tau leakage from cells into the CSF, which may be present even relatively early on in the disease course when clinical symptoms are relatively mild.…”
Section: Discussionmentioning
confidence: 99%
“…4F-H), suggesting their potential to inhibit GSK-3β enzymatic activity. 46 Moreover, the levels of phospho- Tau (Thr217, pTau217, a new biomarker of AD), [47][48][49] phospho-Tau (Thr181, pTau181), and phospho-Tau (Ser396, pTau396), which play major roles in the formation of NFT, 10,50 were decreased by (±)-1, (+)-1, and (−)-1 treatment. These results also suggest that these compounds can inhibit the phosphorylation of tau and its downstream consequence.…”
Section: Resultsmentioning
confidence: 99%
“…At all stages of AD severity, NFTs containing 4R p-tau were more abundant than those containing 3R p-tau while in CTE cases, there was an equivalent amount of 3R and 4R NFTs [ 23 ]. Furthermore, the relative amount of different p-tau epitopes in CTE and AD frontal cortex were found to differ in a study of homogenised tissue (not included in this review due to absence of histology) [ 81 ]. This study found tau phosphorylated at serine 202 (p-tau 202 ) was more abundant in CTE cases and significantly associated with increased years of head injury exposure, while tau phosphorylated at serine 396 (p-tau 396 ) was most abundant in AD cases.…”
Section: Resultsmentioning
confidence: 99%
“…This study found tau phosphorylated at serine 202 (p-tau 202 ) was more abundant in CTE cases and significantly associated with increased years of head injury exposure, while tau phosphorylated at serine 396 (p-tau 396 ) was most abundant in AD cases. The ratio of p-tau 202 : p-tau 396 was increased in low and high severity CTE cases compared to AD [ 81 ]. Quantitative NFT phenotyping in different brain regions and using antibodies against different phosphorylation epitopes and tau isoforms may therefore reveal more subtle differences in p-tau pathology between diseases.…”
Section: Resultsmentioning
confidence: 99%